2021
DOI: 10.1111/cdev.13697
|View full text |Cite
|
Sign up to set email alerts
|

Infant vocalizing and phenotypic outcomes in autism: Evidence from the first 2 years

Abstract: Infant vocalizations are early-emerging communicative markers shown to be atypical in autism spectrum disorder (ASD), but few longitudinal, prospective studies exist. In this study, 23,850 infant vocalizations from infants at low (LR)-and high (HR)-risk for ASD (HR-ASD = 23, female = 3; HR-Neg = 35, female = 13; LR = 32, female = 10; 80% White; collected from 2007 to 2017 near Philadelphia) were analyzed at 6, 12, and 24 months. At 12 months, HR-ASD infants produced fewer vocalizations than HR-Neg infants. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…For example, when compared to ER infants with ASD, ER infants without ASD show greater social reciprocity, positive affect, attentiveness, and vocalizations during social interactions (Wan et al, 2019). A recent study by Plate et al (2022) found that ER infants without ASD experienced steeper growth in vocalization production between 6 and 24 months when compared to both ER infants with ASD and LR infants. These traits may elicit better quantity and quality of language from parents, regardless of their education level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when compared to ER infants with ASD, ER infants without ASD show greater social reciprocity, positive affect, attentiveness, and vocalizations during social interactions (Wan et al, 2019). A recent study by Plate et al (2022) found that ER infants without ASD experienced steeper growth in vocalization production between 6 and 24 months when compared to both ER infants with ASD and LR infants. These traits may elicit better quantity and quality of language from parents, regardless of their education level.…”
Section: Discussionmentioning
confidence: 99%
“…This trend seems to be recovered in subsequent items (second and third years), in relation to the greater interest in visuo‐perceptual processing and activities compared to the verbal ones, facilitating compensation strategies that favor learning and success in tasks mediated by visual‐perceptual support, not requiring direct and constant interaction with the examiner. It has been widely described that social and communication concerns for children with suspected ASD become evident very early during development, between 12 and 18 months of age (Salgado‐Cacho et al, 2021; Plate et al, 2022), with some early signs also before (Chericoni et al, 2016; Davidovitch et al, 2018) and are the target of early intervention to at‐risk infants. On the other hand, children with ASD notably benefit by the presentation of visual support during cognitive performances (Samson et al, 2012); moreover, relative strengths in visuo‐spatial and abstract reasoning and visual working memory have been described in children with ASD at different ages as a possible specific marker of their intellectual functioning (Audras‐Torrent et al, 2021; Mouga et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At 12 months, the CSBS was selected for annotation if it was completed and available. The CSBS was selected because it is longer than the AOSI and thus provides more data, and also to facilitate longitudinal comparisons with vocalizations produced at 24 months during the CSBS as part of a larger coding effort [ 51 ]. If a CSBS was not available (due to recording failure or the missing/incomplete administration), the AOSI was used.…”
Section: Methodsmentioning
confidence: 99%
“…Rater training included a presentation on the coding pipeline, a requirement that raters establish greater than 80% agreement on a set of gold-standard training reliability files, and a requirement to attend periodic reliability meetings. This pipeline is described further in [ 51 ].…”
Section: Methodsmentioning
confidence: 99%